Perbedaan Kualitas Tidur antara Pasien Asma dengan Pasien PPOK di RSUD Dr. Moewardi - Ratmilia, Rizka; Setijadi, Ana Rima; ., Widardo (Nexus Kedokteran Klinik, 2014)
Asthma and Chronic Obstructive Pulmonary Disease (COPD) refer to group of airflow obstruction diseases characterized by fundamental physiologic problems, they are increased resistance to airflow as a result of caliber reduction of conducting airways and chronic airway inflammation. Sleep requirement is so important for everyoneâs life quality, however their sleep need depends upon many factors such as physiological factors. Asthma and COPD patients may suffer nocturnal symptom or other typical symptom presentation. This study aimed to find out the difference of sleeping quality between asthmatic patients and COPD patients. This study was an analytical observational with cross-sectional approach. The subjects were selected by purposive sampling technique. A total of 60 subjects consisted of 30 asthmatic patients and 30 COPD patients from outpatients who visited the pulmonary clinics of RSUD DR. Moewardi from April to May 2013. The data were collected using direct interview to fill KSPBJ-IRS (Kelompok Studi Psikiatri Bilogik Jakarta-Insomnia Rating Scale) questionnaire. Furthermore, the data were analyzed using Chi-Square test on Statistical Product and Service Solution (SPSS) 20.00 for Windows. There is no significant difference of sleep quality between asthmatic patients and COPD patients. According to Chi-Square test results, p-value is 0,301; p > 0,05. From this study it can be concluded that the obtained, there is no difference of sleep quality between asthmatic patients and COPD patients. Keywords: Sleep Quality, Asthma, COPDÂ